The ecosystem of a residential district: problems, development prospects - Olga N. D’Yachkova (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. The problem of antagonistic contradiction between human life and the environment has been turning global along with the development of urbanization, breakthrough growth of the energy and technological potency of cities, leading to an increase in the consumption of natural resources and an impact on the biosphere. All over the world and in Russia, scientists are searching for environmentally friendly technologies for urban planning, housing and utilities sectors. However, the problem of analyzing and forecasting the state of ecosystems in residential areas and their influence on man and the environment remains unresolved and needs to be solved in many settlements.Materials and methods. The article analyzes the legal and regulatory documentation on design and construction, urban planning solutions for residential areas, architectural and structural solutions for apartment buildings, statistical and analytical reports on housing construction in Russia, presented on the Internet.Results. The proposed subjects for discussion include two concepts of the term “ecosystem”, results of the analysis of indicators of housing construction in Russia, indices of the quality of the urban environment in settlements, and a factor model used to assess the ecosystem of a residential area. A lifecycle model of a residential area, that represents a complex system, composed of capital construction facilities, linear facilities, landscaping and gardening, and waste management, is used as the basis for the generalization of well-known approaches, developed from the standpoint of the system analysis. Properties of interaction between facilities, on the one hand, facilities and the environment, on the other hand, are taken into account.Conclusions. Now residential housing is constructed faster, and urban areas, occupied by residential buildings, grow accordingly in the settlements of the Russian Federation willing to provide their population with high-quality housing. Mass construction of apartment buildings continues to be the main focus of the country’s urban development. Urban planning activities, aimed at the development and maintenance of residential areas, need all the more attention. It is important to use the biosphere approach, supported by the regulatory and technical framework of construction and operation of facilities and the urban planning environment, to solve the problem of nature conservation and human health maintenance.